Chromatin reconstruction during mouse terminal erythropoiesis - Honghao Bi; Ye Hou; Juan Wang; Zongjun Xia; Dongmei Wang; Yijie Liu; Haiyan Bao; Xu Han; Kehan Ren; Ermin Li; Feng Yue; Peng Ji (iScience, 2022)
Summary: Mammalian terminal erythropoiesis involves chromatin and nuclear condensation followed by enucleation. Late-stage erythroblasts undergo caspase-mediated nuclear opening that is important for nuclear condensation through partial histone release. It remains unknown the dynamic changes of three-dimensional (3D) genomic organization during terminal erythropoiesis. Here, we used Hi-C to determine the chromatin structural change during primary mouse erythroblast terminal differentiation. We also performed RNA-sequencing and ATAC-sequencing under the same experimental setting to further reveal the genome accessibility and gene expression changes during this process. We found that late-stage terminal erythropoiesis involves global loss of topologically associating domains and establishment of inter-chromosomal interactions of the heterochromatin regions, which are associated with globally increased chromatin accessibility and upregulation of erythroid-related genes.